The outcomes of proximal femur replacement with hemiarthroplasty after tumor resection in individuals with Parkinson's disease - Zhao, Zhiqing; Wang, Jichuan; Guo, Yu; Niu, Jianfang; Guo, Wei; Yang, Rongli; Yan, Taiqiang; Tang, Xiaodong (Frontiers in Surgery, 2023)
Background: Patients with neurological disorders often experience a high incidence of postoperative complications following proximal femur replacement (PFR) surgery. The orthopaedist faces a significant difficulty in treating parkinson’s disease (PD) because of the weakened bone condition, excessive muscle tension, and increased risk of fractures. The objective of this research is to assess the impact of PD on PFR following tumor removal. Methods: A retrospective study was conducted from 2010 to 2020, focusing on a solitary institution, analyzing 9 patients diagnosed with PD who underwent PFR with hemiarthroplasty as a result of tumor removal. The study consists of 2 men and 7 women, with an average age of 71 (SD, 12) years. We assessed the outcomes after surgery in terms of pain management, quality of life, functional ability, occurrence of complications, and survival durations. Results: All nine patients underwent planned surgeries. Intraoperative complications was not observed. The average length of the follow-up period was 24 (SD, 20) months, ranging from 8 to 72 months. Despite the fact that 8 patients passed away due to tumor progression, the endoprostheses were still well at that point. The preoperative VAS score of 7 (SD, 1.87) decreased to a postoperative score of 2 (SD, 1.32). The KPS was improved to73 (SD, 7) from 52 (SD, 14), postoperatively. Post-surgery, there were notable enhancements in both pain levels and the overall quality of life scores. Following the surgical procedure, individuals are able to ambulate steadily, resuming their regular daily routines. Living patients had an average MSTS score of 21 (SD, 2.5), ranging from 17 to 25. In total, there were four (44.4%) patients suffered complications after surgery, comprising of one wound dehiscence, one prosthetic fracture, one hip dislocation, and one local recurrence. Conclusions: Significant improvements in function and pain relief can be achieved through PFR with hemiarthroplasty following tumor removal in patients with PD. The implementation thorough preparation and carefull nursing results in reduced complications and improved outcomes in PD patients.